A cluster of health care workers with COVID-19 pneumonia caused by SARS-CoV-2 - Wei, Xiao-Shan; Wang, Xiao-Rong; Zhang, Jian-Chu; Yang, Wei-Bing; Ma, Wan-Li; Yang, Bo-Han; Jiang, Nan-Chuan; Gao, Zhan-Cheng; Shi, Huan-Zhong; Zhou, Qiong (Journal of microbiology, immunology and infection, 2021)
The current outbreak of coronavirus disease 2019 (COVID-19) caused by Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Wuhan, Hubei, China, spreads across national and international borders. We prospectively collected medical records of 14 health care workers (HCWs) who were infected with SARS-CoV-2, in neurosurgery department of Wuhan Union Hospital, China. Among the 14 HCWs, 12 were conformed cases, the other 2 were suspected cases. Most of them were either exposed to the two index patients or infected coworkers, without knowing they were COVID-19 patients. There were 4 male and 10 female infected HCWs in this cohort, whose mean age was 36 years (SD, 6 years). The main symptoms included myalgia or fatigue (100%), fever (86%) and dry cough (71%). On admission, 79% of infected HCWs showed leucopenia and 43% lymphopenia. Reduced complement C3 could be seen in 57% of the infected HCWs and IL-6 was significantly elevated in 86% of them. The proportion of lymphocytes subsets, concentrations of immunoglobulins, complement C4, IL-2, IL-4, IL-10, TNF-α and IFN-γ were within normal range in these 14 infected HCWs. The most frequent findings on pulmonary computed tomographic images were bilateral multifocal ground-glass opacifications (86%). Human-to-human transmission of COVID-19 pneumonia has occurred among HCWs, and most of these infected HCWs with confirmed COVID-19 are mild cases. Our data suggest that in the epidemic area of COVID-19, stringent and urgent surveillance and infection-control measures should be implemented to protect doctors and nurses from COVID-19 infection.